Embedding Academic Support within an Academic Discipline: A Teaching Model - Morton McKay, Tracey Jill (South African Journal of Higher Education, 2016)
An innovative teaching intervention model involving the integration of geographical content into academic literacy programmes and visa versa is reported upon. This model involved the ‘movement’ of academic literacy support as an independent and isolated function of the Academic Development and Support Division (ADS) to one fully integrated into an academic discipline. The process of collaboration was driven by the lecturer, by actively engaging with the ADS facilitators on a continuous basis. This sustained the intervention by directing the nature of the academic support required. In the end, the sharing of ADS and discipline specific duties, as staff ‘boundary hopped’ between disciplines, allowed both for the co-creation of curricula and a true teaching partnership to evolve. Both ADS and the academic discipline were enriched, to the benefit of staff and students.